2016
DOI: 10.1039/c5cp05974g
|View full text |Cite
|
Sign up to set email alerts
|

Probing the early stages of solvation of cis-pinate dianions by water, acetonitrile, and methanol: a photoelectron spectroscopy and theoretical study

Abstract: cis-Pinic acid is one of the most important oxidation products of α-pinene--a key monoterpene compound in biogenic emission processes. Molecular level understanding of its interaction with water in cluster formation is an important and necessary prerequisite for ascertaining its role in the aerosol formation processes. In this work, we studied the structures and energetics of the solvated clusters of cis-pinate (cis-PA(2-)), the doubly deprotonated dicarboxylate of cis-pinic acid, with H2O, CH3OH, and CH3CN by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 55 publications
2
25
0
Order By: Relevance
“…Figure 3 presents the NIPE spectra of cis-PA 2− (H 2 O) n (n = 0−4) clusters and their optimized low-lying structures. 26 A close inspection of the spectra unveils interesting odd−even variations with the water number for both EBEs and spectral band shapes. The spectra show that the odd number added H 2 O (first and third) shifts the spectrum to high EBE by ∼0.3 eV and broadens the spectral features by 30%, compared to a shift of ∼0.6 eV to high EBE by the even number added H 2 O (second and fourth).…”
Section: Organic Ion−water Clusterssupporting
confidence: 69%
See 1 more Smart Citation
“…Figure 3 presents the NIPE spectra of cis-PA 2− (H 2 O) n (n = 0−4) clusters and their optimized low-lying structures. 26 A close inspection of the spectra unveils interesting odd−even variations with the water number for both EBEs and spectral band shapes. The spectra show that the odd number added H 2 O (first and third) shifts the spectrum to high EBE by ∼0.3 eV and broadens the spectral features by 30%, compared to a shift of ∼0.6 eV to high EBE by the even number added H 2 O (second and fourth).…”
Section: Organic Ion−water Clusterssupporting
confidence: 69%
“…Clusters with tailored compositions and precisely controlled sizes are ideal in providing microscopic information on macroscopic phenomena and offer the unique opportunity to untangle the complex intermolecular interactions and thermodynamics important to the formation of critical nuclei during NPF. ,, They are also tractable with first principle calculations, and in turn, the experimental data on those clusters can reinforce the improvement of theoretical models and methods.…”
Section: Cluster Synthesis Analysis and Spectroscopic Characterizationmentioning
confidence: 99%
“…[8] We have been interested in characterizing the small pre-nucleation clusters relevant to NPF, especially organic acid containing clusters, by combining negative ion photoelectron spectroscopy (NIPES) and quantum chemical calculations. [30][31][32][33][34][35][36][37] For example, we have shown that succinic acid molecule, HO 2 C(CH 2 ) 2 CO 2 H, is capable of stabilizing the bisulfate ion HSO 4 − and its own conjugate base succinate ion, HO 2 C(CH 2 ) 2 CO 2 − , indicating significant thermodynamic advantage of organic molecules in promoting bisulfate clusters and organic aerosol particles formation. [30,34] Most recently, we have studied the deprotonated sulfuric acid-formic acid anionic cluster [H 2 SO 4 •HCOOH−H + ] − , and found that the charge delocalization accompanying formation of two strong hydrogen bonds is strong enough to compensate the proton affinity imbalance in forming H 2 SO 4 •HCOO − cluster.…”
Section: Introductionmentioning
confidence: 98%
“…We tentatively assign it to higher energy quaternary [Na + , HDC 2 − , OH − , H 2 O] complex, hinging on the hypothesis that such complex may be kinetic trapped. [35][36][37][38][39]…”
Section: Discussionmentioning
confidence: 99%
“…However, it needs to be pointed out that all component ions in both quaternary and ternary complexes [Na + , HDC 2 − , OH − , H 2 O, DC 2 2− ] exist in our sprayed solution, and previous studies have shown that higher energy isomers can often exist even at low temperatures due to kinetic trapping. [35][36][37][38][39] Therefore the existence of such quaternary system remains a possibility, which may contribute to the weak low binding energy band.…”
Section: The Origin Of the Weak Band (X′) Of M + -Dc 2 2-(h 2 O) N (M=na K)mentioning
confidence: 99%